An introduction to numerical analysis for electrical and computer engineers - Zarowski, Christopher J. (Wiley, 2004)
* This book is an introduction to numerical analysis and intends to strike a balance between analytical rigor and the treatment of particular methods for engineering problems* Emphasizes the earlier stages of numerical analysis for engineers with real-life problem-solving solutions applied to computing and engineering* Includes MATLAB oriented examples.